Satire 6 - Iuvenalis, Decimus Iunius (Cambridge Greek and Latin classics, 2014)
"Juvenal's sixth Satire is a masterpiece of comic hyperbole, an outrageous rant against women and marriage which, in its breadth and density, represents the high point of the misogynistic literature of classical antiquity. The Introduction situates Juvenal within the wider tradition of Roman satire, interrogates afresh the poem's architecture and recurrent themes, shows how Juvenal systematically attributes to his monstrous women the inverse of the Roman wife's canonical virtues, traces the various literary currents which infuse the Satire, and lastly addresses the much-discussed issue of the poetic voice or persona from a sociohistorical as well as a theoretical perspective. Above all, the commentary strives to locate Juvenal in his historical, literary and cultural context, while simultaneously affording assistance with the nuts and bolts of the Latin, and always keeping in view two key questions: what was Juvenal's purpose in writing the Satire? How seriously was it meant to be taken?"--